For Better or Worse? Subjective Expectations and Cost-Benefit Trade-Offs in Health Behavior - Gabriella Conti; Pamela Giustinelli (Institute of Labor Economics (IZA), 2023)
We provide a framework to disentangle preferences and beliefs in health behavior and apply it to lockdown compliance in the UK. We estimate a model of compliance choice with uncertain costs and benefits to quantify utility tradeoffs, decompose group differences in compliance, and compute monetary compensations for complying. Individuals have largest disutility from passing away from COVID and being caught transgressing, and largest utility from preserving their mental health. While preferences and beliefs explain compliance differences by gender, only preferences drive differences by vulnerability. When others fail to comply and trust breaks down, the risk tolerant and those without prior COVID experience comply less, the vulnerables more. When a public figure breaches the rules, opponents comply less. Heterogenous beliefs, preferences, and responses to others are key to health policies.
Keywords: C25; C83; D84; I12; I18; 330; health behaviors; beliefs; preferences; COVID-19